Assessment of the diet of 0- to 6-year-old children in municipal schools in a Brazilian city - Garbin, Clea Adas Saliba [UNESP]; Arcieri, Renato Moreira [UNESP]; Ferreira, N. F. [UNESP]; Luvizuto, E. R. [UNESP]; Alle, C. F. [UNESP] (My University, 2005)
Diet control is one of the important factors in the prevention of dental caries because food functions as substratum for fermentation and, consequently, for the formation of the organic acids that demineralize the tooth surface. This study aims to descriptively assess school diet and the associated caries-preventive methods applied to children in all municipal nursery schools of a Brazilian city (Aragatuba/SP). For this, a questionnaire with open and closed questions was used. The results showed that all schools serve school meal, which is composed mainly of sugar, carbohydrates, and proteins. The students enjoy the meal very much because for most of them, the meal served at school is the only source of food. It was observed that 90% of the schools offer other kinds of food besides the main school meal. The snacks served such as cakes, white hominy, and milk fudge are composed of sweet and highly cariogenic foods. It was also verified that in 13.30% of the schools, the daily supervised dental hygiene, an important procedure that should not be neglected, is not carried out. This procedure introduces the children to healthy habits that are added to those acquired in the family environment. It was concluded that the school diet is potentially cariogenic and, in association with the lack of daily dental hygiene, this potential may become even higher.
Keywords: Diet; Oral hygiene; Sugar; sugar; animal; beverage; Brazil; cacao; carbohydrate diet; carbonated beverage; cariogenic diet; catering service; child; cross-sectional study; dental caries; diet; feeding behavior; human; infant; milk; mouth hygiene; nursery school; preschool child; protein intake; questionnaire; sugar intake; Animals; Beverages; Cacao; Candy; Carbonated Beverages; Child; Child, Preschool; Cross-Sectional Studies; Dental Caries; Diet, Cariogenic; Dietary Carbohydrates; Dietary Proteins; Dietary Sucrose; Food Habits; Food Services; Humans; Infant; Milk; Oral Hygiene; Questionnaires; Schools, Nursery